Link quality based path delay analysis in wireless sensor networks - Quan CHEN; Hong GAO (Tongxin xuebao)
The upper bound of the probability of a path meeting the deadline was given based on link quality, of which the time complexity was proved to be exponential. Moreover, the greedy algorithm (RROP) was proposed to maximize the end-to-end packet deliver ratio under a given deadline, considering the quality of each link. The RROP algorithm optimizes the end-to-end packet deliver ratio by setting the maximum number of retransmissions of each link along the path based on the deadline and link quality. It was proved that the proposed method can find the optimal solution in a polynomial time, and with which could achieve an approximate optimal lower bound of the probability for a path meeting the deadline. Finally, the experimental results show that the upper and lower bounds are accurate, and the proposed algorithm can perform 10% better than the traditional method, in terms of energy consumption and delay.